Measuring Laser Beams with a Neural Network (Data) - Hofer, L; Krstajic, M; Smith, R P (University of Oxford, 2022)
The data for the the paper "Measuring Laser Beams with a Neural Network." The readme.txt file in main directory gives a detailed explanation of the data contents and structure. See https://github.com/Dipolar-Quantum-Gases/nn-beam-profiling for code pertaining to the dataset and the paper.